Model reference adaptive control of an independent steer-by-wire system: A simulation using a 14-Degree-of-Freedom vehicle model - Ahmad, Fauzi; Hamdi, Muhammad Haziq; Che Hasan, Mohd Hanif; Harun, Mohamad Hafiz; Harun, Mohd Hanif; Aparow, Vimal Rau (Penerbit Universiti Malaysia Pahang, 2024)
This research delves into how Model Reference Adaptive Control (MRAC) can be applied in an independent Steer-by-Wire (SBW) system, utilising a detailed 14 Degrees of Freedom (DOF) full-vehicle model. This study is all about pushing forward vehicle dynamicsand control using SBW technology. This study also has come up with some cutting-edge control algorithms that allow each wheel to be steered independently, which seriously boosts how manoeuvrable and responsive the vehicle is. Through simulations, the study shows that MRAC is a big improvement over traditional control methods where quantitative analysis shows that MRAC reduces yaw rate errors by up to 66.67% compared to Proportional-Integral-Derivative (PID) and 50% compared to Multi-order PID (MOPID). Additionally, in lateral acceleration and sideslip angle controls, MRAC demonstrates a similar reduction in errors, significantly outperforming PID and MOPID with errors maintained well below 10%,proving its worth in predictive control and real-time adaptability to various road conditions and driver intentions. The key finding from this study is that MRAC greatly enhances manoeuvrability and responsiveness compared to standard methods which offer flexibility according to the different driving scenarios. There re notable advancements in vehicle steering systems, which contribute to safer and more efficient driving. In essence, this work marks a significant step forward in automotive steering technology, opening the door to safer and more efficient modern vehicles.